2020
DOI: 10.1136/bmj.m3975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Athena SWAN funding incentives on women’s research leadership

Abstract: Is it difficult being a woman scientist?" the biochemist Dorothy Crowfoot Hodgkin was asked at high table dinner in an Oxford college by the man sitting next to her. "Not since I won the Nobel Prize," she replied. 1 In 1964, the British press had reacted to her award with the headlines: "Oxford housewife wins Nobel" and "British woman wins Nobel Prize-£18 750 prize to mother of three." 2 While such overtly sexist treatment of female scientists by the media is now rare, progress towards gender equality in unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…Ovseiko and colleagues cite evidence that gender diversity is important because it delivers research that is more interdisciplinary, higher quality, more rigorous, and more relevant 1. Studies have shown that women leaders get higher scores than men in multisource feedback exercises used in the UK to support the appraisal process 3.…”
Section: Long Way To Gomentioning
confidence: 99%
See 2 more Smart Citations
“…Ovseiko and colleagues cite evidence that gender diversity is important because it delivers research that is more interdisciplinary, higher quality, more rigorous, and more relevant 1. Studies have shown that women leaders get higher scores than men in multisource feedback exercises used in the UK to support the appraisal process 3.…”
Section: Long Way To Gomentioning
confidence: 99%
“…The BMJ analysis article examining the effect of gender diversity incentives in the UK’s National Institute of Health Research (NIHR) funding awards process (doi:10.1136/bmj.m3975)1 has come at an interesting time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23 The profile of gender equity in higher education and research has been raised by the introduction of Athena SWAN-linked funding incentives by the NIHR. [26][27][28][29] While Athena SWAN awards are useful markers of achievement for higher education institutions and research centres and institutes, they alone are insufficient to assess and monitor the progress of NIHR BRCs towards gender equity. 30 In this regard, tracking of the proportion of women and rate of their achievements is important; however, it is not routinely recorded in NIHR BRCs.…”
Section: Introductionmentioning
confidence: 99%
“…Since its inception in 2011 the Athena SWAN initiative has had a substantial effect on the proportion of grants going to female researchers and their teams, say Pavel Ovseiko and colleagues. Because of the way women tend to operate, this has meant research that is more multidisciplinary, rigorous, relevant, and honest 4…”
mentioning
confidence: 99%